Effect of fungicides on seed quality of lentil (Lens culinaris L.) during storage (Jahangirnagar University Journal of Biological Sciences, 2017)
Laboratory tests were carried out to study the effect of different fungicides i.e. Bavistin DF, Vitavax and Genuine 50WP on the seed quality of lentil during storage condition. After processing and drying, seeds were preserved separately with three fungicides at the rate of 2.5g kg-1 of seeds and stored in earthen pots till next planting time. The seed quality i.e. moisture content (%), germination rate (%), dry weight (g) of seedlings and vigour index were measured at the end of storage period. The average germination percentage of the initial seed lot was 90% and moisture content was 9%. Among the three fungicides, Bavistin DF showed higher values for germination percentage (91.3% in 2004 and 92.7% in 2005), dry weight (0.70 g in 2004 and 0.67 g in 2005) and vigour (63.8 in 2004 and 62.1 in 2005).Jahangirnagar University J. Biol. Sci. 5(2): 51-56, 2016 (December)